(untitled) (CIPEEX, 2025)
This research aims to demonstrate that workers in situations of social vulnerability and extreme poverty are easy targets in the context of slave-like work. Considering that the exploitation of labor in various branches of the economy takes advantage of the precarious living conditions of citizens, it was possible to see that the inclusion of people in degrading working conditions is directly related to their poor financial condition. Workers who need to provide for themselves and their families are attracted by promises of better living conditions. Through the literature review, it became clear that these workers, upon arriving at their jobs, are faced with inhumane conditions and precarious work facilities. In the workplace, they encounter constant debt, as they need to cover their expenses and work materials, remaining in a cycle of debt and exploitation that is renewed day after day. In this way, it was possible to conclude that social vulnerability ends up being a direct path for workers to be exploited with degrading work, exhausting working hours and few or even no decent working conditions and structures. In other words, in addition to not receiving, or receiving negligible amounts of money, they are still not covered by the guarantees provided for in labor legislation and are exposed to inhumane, unhealthy, dangerous and undignified conditions. These workers suffer, in addition to the exploitation of their workforce, physical and moral violence from their employers.